2021
DOI: 10.17705/1cais.04845
|View full text |Cite
|
Sign up to set email alerts
|

How to Conduct Rigorous Supervised Machine Learning in Information Systems Research: The Supervised Machine Learning Report Card

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication in the Communications of the Association for Information Systems. We are providing this early version of the manuscript to allow for expedited dissemination to interested readers. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered, which could affect the content. All legal discla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Interestingly, as of today, many AI-based information systems remain static, i.e. employ once-trained ML models (Kühl et al, 2021). With increasing focus on deployment and life cycle management, we will see more adaptive AI-based systems that sense changes in the environment and use ML to learn continuously (Baier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as of today, many AI-based information systems remain static, i.e. employ once-trained ML models (Kühl et al, 2021). With increasing focus on deployment and life cycle management, we will see more adaptive AI-based systems that sense changes in the environment and use ML to learn continuously (Baier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[95] Some major software companies, such as Google [96] or Microsoft, [97] have synthesized best practices in the large-scale development of data-driven applications. From the information system research community, Kühl et al [98] confirmed the same challenge. Even with full access to data, the researchers cannot evaluate or replicate the results due to the inconsistency in the documentation and reporting of ML studies.…”
Section: Research Perspectivesmentioning
confidence: 94%
“…Some major software companies, such as Google [96] or Microsoft, [97] have synthesized best practices in the large‐scale development of data‐driven applications. From the information system research community, Kühl et al [98] . confirmed the same challenge.…”
Section: Research Perspectivesmentioning
confidence: 95%
See 2 more Smart Citations